Rehabilitation of the disabled adolescent: experience with a local authority assessment centre. Issue 6494 (24th August 1985) - Newton, P; Swinson, D R; Bruce, K
Abstract : School leavers and young adults who are severely physically disabled pose particular problems for habilitation and rehabilitation. A local authority unit, the Fourways Assessment Centre, has been providing a comprehensive service to this group of people for the past 10 years. Rather than operating as an independent self contained unit it has been closely integrated with the local authority social services and educational services.